Application of Network Pharmacology in the Treatment of Neurodegenerative Diseases with Traditional Chinese Medicine - Chen, Qiang; Chen, Guanghui; Wang, Qianyan (Planta Medica, 2025)
In recent years, the incidence of neurodegenerative diseases, including Alzheimerʼs disease, Parkinsonʼs disease, Huntingtonʼs disease, and amyotrophic lateral sclerosis, has exhibited a steadily rising trend, which has posed a major challenge to the global public health. Traditional Chinese medicine, with its multicomponent and multitarget characteristics, offers a promising approach to treating neurodegenerative diseases. However, comprehensively elucidating the complex mechanisms underlying traditional Chinese medicine formulations remains challenging. As an emerging systems biology method, network pharmacology has provided a vital tool for revealing the multitarget mechanisms of traditional Chinese medicine through high-throughput technologies, molecular docking, and network analysis. This paper reviews the advancements in the application of network pharmacology in treating neurodegenerative diseases using traditional Chinese medicine, analyzes the current status of relevant databases and technological methods, discusses the limitations, and proposes future directions to promote the modernization of traditional Chinese medicine and the development of precision medicine.
Keywords: neurodegenerative diseases; traditional Chinese medicine; network pharmacology; therapeutic targets